Comportamiento y salud de los jóvenes universitarios: satisfacción con el estilo de vida - Lema Soto, Luisa Fernanda (2022)
The purpose of this study was to describe behaviors that form part of the life-style of young college students in 10 dimensions: exercise and physical activity, leisure time, self-care and medical care, diet, alcohol, tobacco and illegal drug consumption, sleep, sexuality, interpersonal relationships, coping and perceived emotional state, and their satisfaction with each. 598 students participated (44.7% men and 55.3% women) from a private university in the southwest of Colombia, who answered the College Youth Lifestyle Questionnaire (Cevju). The results show a high prevalence of healthy practices in all dimensions, except for exercise and physical activity, and satisfaction with lifestyle and general health  status. There was coherence between the level of satisfaction and practices (healthy or unhealthy), and this relationship was analyzed following the guidelines of the stages of change model. Finally, some ideas are presented for consideration, with the idea of creating intervention programs aimed at promoting positive health behaviors and preventing those that adversely affect health.